Perlindungan Hukum Terhadap Data Konsumen Yang Melakukan Pinjaman Melalui Aplikasi Online Di Gorontalo (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research aims to find out what form of legal protection there is for consumer data who make loans through online applications in Gorontalo and to find out what efforts consumers can take if there is a dispute with the lender regarding leakage of consumer data. This research is empirical normative legal research conducted at the Gorontalo Regional Police and victims of data misuse by online loans. Primary data and secondary data obtained through library research and field research were then analyzed qualitatively. The research results show that the form of legal protection for consumer data who make loans through online applications in Gorontalo is carried out in three forms, namely: first, protection through regulations, namely in the Personal Data Protection Law, the Consumer Protection Law, and Article 1338 of the Civil Code. Second, protection through law enforcement efforts carried out by the police, as well as preventing misuse of data through legal education as a form of preventive legal protection. Meanwhile, efforts that consumers can take if there is a dispute with a lender regarding leakage of consumer data are legal action taken by the police through reporting complaints from the public to investigations that follow up on complaints from the public, and monitoring and taking action carried out by the OJK as parties who carry out activities regarding the implementation of non-bank banking institutions such as online loans.